Der Zorn des ehrlichen Mannes. Die Neudeutung von Molières 'Misanthrope' in der 'Deutschen Schaubühne - Steigerwald, Jörn (Theater-Transfers. Akkulturationen des europäischen Dramas in Gottscheds 'Deutscher Schaubühne')

ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730). Einleitung. - Steigerwald, Jörn (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Trendbericht Organische Chemie 2022 - Andexer, Jennifer N.; Beifuss, Uwe; Brasholz, Malte; Breinbauer, Rolf; Breugst, Martin; Dumele, Oliver; Ernst, Martin; Ganardi, Ruth; Giese, Michael; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Synthesis of Bifunctional Phosphonium Salts Bearing Perfluorinated Side Chains and Their Application in the Synthesis of Cyclic Carbonates from Epoxides and CO 2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (Asian Journal of Organic Chemistry)
Keywords: Organic Chemistry

Cover Feature: Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives (Chem. Eur. J. 23/2022) - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Cover Picture: Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates (Angew. Chem. Int. Ed. 31/2022) - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Frustrated Lewis Pair‐Catalyzed Hydroboration of Nitriles: FLP Versus Borenium Catalysis - Sieland, Benedikt; Hoppe, Axel; Stepen, Arne J.; Paradies, Jan (Advanced Synthesis & Catalysis)
Keywords: General Chemistry

Was ist und was leistet hermeneutische Ethik? - Schmidt, Jochen (Ethik in der Hermeneutik - Hermeneutik in der Ethik)

Was wir uns schulden: Freiheit und Pflichten gegen sich selbst - Schmidt, Jochen

Mental rotation with colored cube figures - Rahe, Martina; Weigelt, Matthias; Jansen, Petra (Consciousness and Cognition)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology

Stating Comparison Score Uncertainty and Verification Decision Confidence Towards Transparent Face Recognition - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Damer, Naser; Kuijper, Arjan (33nd British Machine Vision Conference 2022)
Keywords: Computer Vision and Pattern Recognition (cs.CV); FOS: Computer and information sciences; FOS: Computer and information sciences

Familienbildung und Ungleichheit: Sozialraumtheoretische Perspektiven auf das (Nicht)Erreichen von Eltern - Landhäußer, Sandra; Faas, Stefan (Familienbildung – Praxisbezogene, empirische und theoretische Perspektiven)
Familienbildung ist ein Arbeitsfeld, auf das sich zunehmend Aufmerksamkeit richtet. Der Diskurs wird intensiver; von Bildungs-, Familien- und Jugendhilfepolitik wird sie als wichtige Akteurin adressiert. Zugleich steht sie vor großen strukturellen, personellen und inhaltlichen Herausforderungen. Das traditionelle Spannungsverhältnis zwischen Erwachsenenbildung und Kinder- und Jugendhilfe erhält neue Brisanz. Der vorliegende Band entfaltet differenzierte Fragestellungen und eröffnet Perspektiven – mit Schwerpunkten auf Politische Familienbildung und Professionalisierung.
Keywords: Familie | Erwachsenenbildung | Jugendhilfe | Markt | Soziale Arbeit

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Strain mode-dependent weighting functions in hyperelasticity accounting for verification, validation, and stability of material parameters - Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Optimized material parameters obtained from parameter identification for verification wrt a certain loading scenario are amenable to two deficiencies: Firstly, they may lack a general validity for different loading scenarios. Secondly, they may be prone to instability, such that a small perturbation of experimental data may ensue a large perturbation for the material parameters. This paper presents a framework for extension of hyperelastic models for rubber-like materials accounting for both deficiencies. To this end, an additive decomposition of the strain energy function is assumed into a sum of weighted strain mode related quantities. We propose a practical guide for model development accounting for the criteria of verification, validation and stability by means of the strain mode-dependent weighting functions and techniques of model reduction. The approach is successfully applied for 13 hyperelastic models with regard to the classical experimental data on vulcanized rubber published by Treloar (Trans Faraday Soc 40:59–70, 1944), showing both excellent fitting capabilties and stable material parameters.
Keywords: Mechanical Engineering

Goal-oriented error estimation and h-adaptive finite elements for hyperelastic micromorphic continua - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics